Purificação da Cefamicina C por processo de adsorção em coluna de leito fixo - Oliveira, Liliane Maciel de (2013)
Cephalosporins are β-lactam antibiotics which are widely used in the treatment of bacterial infections. Within this group, cephamycin C (CefC) stands out from the others cephalosporins antibiotics due to its greater resistance to β-lactamases enzymes and its broader spectrum of action against Gram-negative pathogens. It is produced by the bacteria Nocardia lactamdurans and Streptomyces clavuligerus, usually in submerged fermentation. In the literature, the available information about the purification processes of this antibiotic are restricted to patents or papers published in the past decades. As cefC is the raw material for the production of important semi-synthetic antibiotics and due to the lack of scientifically substantiated information about its separation and purification processes, the motivation for the development of this thesis has arisen. Then, the aim of this thesis was to study the purification process of CefC produced by S. clavuligerus, by using the processes of adsorption and ion exchange in fixed bed columns. The techniques of adsorption and ion exchange present themselves as good strategies for CefC purification due to the amphoteric nature of the antibiotic molecule, which has positive or negative charges depending on the environmental pH, and the bicyclic nucleus in its structure, which allows the interaction with hydrophobic structures. As there is no chemical standard of cefC available on the market, in this study we have only used culture broth containing this antibiotic. The adsorbents evaluated were the neutral resins Amberlite XAD4 and Amberlite XAD16 and the anionic resin Q Sepharose XL. At first, ion exchange column experiments using the resin QXL were carried out. The results showed that the variation of the flow rate in the range of 2.5 mL/min to 7.5 mL/min did not affect the efficiencies of product recovery nor of bed utilization, and it did not interfere with the bioactive compounds elution. The isocratic elution modes using 0.1% or 1% NaCl (w / v) were able to separate cefC from other (s) compound (s) with antimicrobial activity present in the broth, which were not identified. But the use of 1% NaCl solution promoted the antibiotic recovery in a shorter process time and smaller volume than using 0.1 % NaCl solution. After analysis by mass spectrometry, carried out by ESI ionization in the positive mode, it was observed that the ion exchange process with QXL resin followed by adsorption on a C18 SPE cartridge were able to separate cefC from compound (s) whose molecules after ionization acquired m/z ratios corresponding to the lysine s molecule, and they also reduced the concentration of contaminants with m/z ratios corresponding to the molecules of penicillin N, deacetylcephalosporin C and deacetoxycephalosporin C. As the ion exchange studies were done, the adsorption studies using the neutral resins were initiated. At first, adsorption isotherms of cefC on XAD4 and XAD16 resins were obtained, and the effects of pH and temperature in the adsorption equilibrium were evaluated. The results showed that the broth pH had strong influence on the adsorption and the best condition was observed at pH 2.6 at 15° C. The kinetic experiments have shown that equilibrium is reached more quickly on the resin XAD16. Estimation of intrinsic kinetic parameters and mass transfer coefficients returned higher values for this resin. The column adsorption processes with XAD4 resin, when the column feed consisted of the ultrafiltered or clarified broth and the elution solutions were 1% or 5% (v/v) EtOH solutions, did not lead to separation of cefC from contaminants that were monitored in the experiments. But when the feed consisted of a preAbstract iv purified fraction, obtained in the ion exchange column with QXL resin, added with cephalosporin C, it was possible to separate the two antibiotics. Cephalosporin C was added to simulate the presence of some contaminants in the culture broth - deacetylcephalosporin C and deacetoxycephalosporin C. As these contaminants are in very low concentrations and there are not commercial chemical standards available to purchase, neither an analytical methodology to quantify them, it was decided to add cephalosporin C, whose chemical structure is very similar to the contaminants, the commercial standard is commercially available and there is a quantification method to determinate it. The column experiments with resin XAD16 showed similar results to the experiments with resin XAD4, in which it was also observed the separation of cefC from cephalosporin C. The moment analysis of the chromatographic peaks showed that cefC average retention times and peak dispersions were smaller in the column assays with XAD16 than with XAD4. Thus, a more concentrated fraction containing cefC was obtained in the column experiments with XAD16 resin. Therefore, it was demonstrated by the purification processes studied that the techniques of adsorption and ion exchange were effective in the purification of cefC in relation to contaminants that are difficult to separate